2021
DOI: 10.1186/s12885-021-08374-7
|View full text |Cite
|
Sign up to set email alerts
|

CypB promotes cell proliferation and metastasis in endometrial carcinoma

Abstract: Background The molecular pathogenesis of endometrial cancer is not completely understood. CypB upregulated in many cancers, however, its role in endometrial carcinoma has not been studied. Here, we determine the effect of CypB on the growth of endometrial cancer. Methods In this study, we examined the expression of CypB in endometrial cancer tissues using immunohistochemistry. CypB silenced in HEC-1-B cell line by shRNA. CCK-8, colony formation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The detailed mechanism of action of PPIB/ CypB in carcinogenesis has not yet been fully elucidated. It has been reported that PPIB/ CypB is crucial for proliferation and colony formation and migration of various cancer cells [12,[23][24][25]. Previously, Teng et al demonstrated that CypB expression was significantly higher in NSCLC tissues than in adjacent normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanism of action of PPIB/ CypB in carcinogenesis has not yet been fully elucidated. It has been reported that PPIB/ CypB is crucial for proliferation and colony formation and migration of various cancer cells [12,[23][24][25]. Previously, Teng et al demonstrated that CypB expression was significantly higher in NSCLC tissues than in adjacent normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Seismic waves propagating in fractured media exhibit anisotropic characteristics in terms of attributes such as amplitude, velocity, attenuation, and travel time, which can be used to predict the development intensity of fractures by analyzing their azimuthal variation (Shen et al, 2002;Liu et al, 2021b). Various seismic attributes have different resolutions and different ability to identify fractures (Wang et al, 2022).…”
Section: Seismic Attribute Extractionmentioning
confidence: 99%